Experience in forming entrepreneurial education in Kazakhstan universities in the conditions of information and digital development - Aubakirova, Saltanat; Kozhamzharova, Maira; Zhumabekova, Gaukhar; Artykbayeva, Gulzhan; Iskakova, Zauresh; Zhayabayeva, Ramilya (Frontiers in Education, 2023)
Information and digital technologies can help in shaping the experience of using online courses for student entrepreneurs. This study constitutes an original investigation dedicated to the cultivation of entrepreneurial education experience within Kazakhstani universities, situated within the context of informational and digital development and the contemporary challenges encountered by all nations in the global arena. The main objective of this research was to determine how the academic performance of students studying entrepreneurship through online courses changed over time. The study enrolled 282 second-year and third-year students of the faculty of public administration, business, and law from one Kazakh university. In this study, an experimental design was employed to ascertain the effectiveness of integrating MOOC through the amalgamation of statistical data analysis and paired t-tests. The primary mode of assessment was testing, encompassing closed-end assessments comprising one hundred questions based on the outcomes of a specific course. Each question held a point value of one, with the maximum achievable score being one hundred points. The authors juxtaposed mean scores across different time intervals to ascertain the intervention's impact on student performance. The Student's t-test was utilized to compare the mean values by identifying significant disparities at the 0.05 level. The academic achievements of second-year students in some disciplines improved after the MOOC implementation compared to Point 1. According to the calculations, there was a significant difference in student performance before and after learning with MOOC; the mean score difference and t-value with the paired value are higher than the t-value in the tests of the first and last assessments. Thus, online courses have shown their effectiveness in improving student performance in all ten subjects of the entrepreneurial course. This contributed to improved efficiency of the educational process and the implementation of information and digital technology in the online environment without losing its productivity. This research is of practical value as it indicates the need to integrate information and digital technologies into entrepreneurial education. Educational institutions, curricula, and scientific research may use these findings.